Effects of ingredients and processing conditions on the quality frozen dough bread made from diferent wheat flour - Ruska, Laslo; Timar, Adrian (Acta Agraria Debreceniensis, 2010)
A laboratory scale no-time frozen dough procedure that approximates Romanian commercial practice has been developed and used to study the effects of ingredients and processing conditions on the bread quality of a straight grade wheat flour during prolonged storage (2 days to 26 weeks). All treatments (baking absorption level, mixing energy input, mixer type, fermentation and intermediate proof times, removal of oxidant and/or dough strengthening conditioners and partial freeze-thaw cycles) had significant effects (P<0.05) upon bread quality (loaf volume and/or bread score). In general, these effects were more pronounced with extended frozen storage time. High baking absorption, undermixing, bulk fermentation (> 1 h) and removal of oxidant and/or surfactants had the most dramatic effects. Addition of a very strong flour at 30% to strengthen the wheat flour had no significant effect (P>0.05) upon bread quality under optimum conditions.